Exploring Pronunciation Difficulties in English Vocabulary Among Slow Learners in an Inclusive Classroom - Raifa Naswa Khodijah; Didik Santoso (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates pronunciation difficulties in English vocabulary experienced by a slow learner in an inclusive classroom. The research aimed to identify the types of pronunciation difficulties and the factors influencing them in classroom practice. A qualitative case study design was employed to explore the phenomenon in its natural setting. The participant was one slow learner in a third-grade inclusive elementary classroom, supported by one English teacher as a key informant. Data were collected through three classroom observations, semi-structured interviews, and documentation, then analyzed using thematic analysis. The findings revealed seven pronunciation difficulties grouped into three dimensions: phonological difficulties (elision of final consonants, sound confusion, vowel errors, and difficulty with consonant clusters), orthographic difficulties (spelling-based pronunciation and letter confusion), and affective difficulties (lack of confidence). These difficulties were interconnected and influenced by first language interference, limited phonological awareness, slower information processing, and classroom learning conditions. The study concludes that pronunciation difficulties experienced by slow learners are multidimensional and require differentiated pronunciation instruction, phonological awareness activities, and supportive learning environments in inclusive classrooms. This study contributes to limited research on slow learners in inclusive EFL settings by highlighting the interaction between phonological, cognitive, orthographic, and affective factors in pronunciation learning.